DIFFICULTIES AND WAYS TO OVERCOME THEM IN THE PROCESS STUDYING A FOREIGN LANGUAGE IN SECONDARY SPECIAL EDUCATIONAL INSTITUTION - O.V. Malykhin; M.V. Hildner (Academy of Cognitive and Natural Sciences, 2007)
The article deals with the problem of determining any difficulties and ways of their overcoming in the process of a foreign language learning in a secondary specialized educational establishment.